2017
DOI: 10.1016/j.bpsc.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Ketamine Infusion on Visual Working Memory: Event-Related Potentials

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. ABSTRACT BACKGROUND: Working memory (WM) deficits are a core feature of schizophrenia. Electrophysiological studies suggest that impaired early visual processing may contribute to impaired WM in the visual domain. Abnormal N-methyl-D-aspartate (NMDA) receptor function has been implicated both in WM and in early visual processing deficits in schizophrenia. We investigated whether ketamine, a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 84 publications
(96 reference statements)
4
11
0
Order By: Relevance
“…We therefore propose that the deleterious effects of DISC1 disruption upon excitatory synapses, identified here using the Der1 mutant mouse, contribute substantially to risk of major mental illness in t(1;11) carriers, but can be influenced by the genetic modifiers and/or environmental factors, leading to differing outcomes. This is consistent with a previous observation that, irrespective of diagnosis, all tested t(1;11) carriers exhibit an abnormal schizophrenia endophenotype, the P300 event-related potential 6 , and that P300 abnormalities are linked to NMDAR dysfunction 56 .…”
Section: Discussionsupporting
confidence: 93%
“…We therefore propose that the deleterious effects of DISC1 disruption upon excitatory synapses, identified here using the Der1 mutant mouse, contribute substantially to risk of major mental illness in t(1;11) carriers, but can be influenced by the genetic modifiers and/or environmental factors, leading to differing outcomes. This is consistent with a previous observation that, irrespective of diagnosis, all tested t(1;11) carriers exhibit an abnormal schizophrenia endophenotype, the P300 event-related potential 6 , and that P300 abnormalities are linked to NMDAR dysfunction 56 .…”
Section: Discussionsupporting
confidence: 93%
“…We therefore propose that the deleterious effects of DISC1 disruption upon excitatory synapses, identified here using the Der1 mutant mouse, contribute substantially to risk of major mental illness in t(1;11) carriers, but can be influenced by the genetic modifiers and/or environmental factors, leading to differing outcomes. This is consistent with a previous observation that, irrespective of diagnosis, all tested t(1;11) carriers exhibit an abnormal schizophrenia endophenotype, the 20 P300 event-related potential 6 , and that P300 abnormalities are linked to NMDAR dysfunction 56 .…”
Section: Ampar-induced Depolarisation Initiates Nmdar-dependent Synapsupporting
confidence: 93%
“…According to our evaluation, most of the studies reached good methodological quality, indicating the reported results are quite reliable (Table 2 ). It was specially observed for reports on P300 complex (Watson et al, 2009 ; Mathalon et al, 2014 ), P100 (Koychev et al, 2017 ), N100 (Oranje et al, 2000 , 2002 ; Kort et al, 2017 ), and PPI (van Berckel et al, 1998 ; Heekeren et al, 2007 ). The study of Kreitschmann-Andermahr et al ( 2001 ) could be ranked as having the poorest methodological quality among the included studies, although they report the same null effects of ketamine as Heekeren et al ( 2007 ) using a very similar cognitive task.…”
Section: Discussionmentioning
confidence: 83%
“…Only three studies have assessed the effects of ketamine on N100 and P100. A recent study has shown that ketamine increased visual P100 potentials during encoding and retrieval phases of a working memory task (Koychev et al, 2017 ), whereas another study did not find any effect of ketamine on P100 in a visual emotional-face recognition task (Schmidt et al, 2013 ). However, a prior study reported that ketamine increased N100 amplitudes in an auditory paradigm (Umbricht et al, 2000 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation